Differences in Complications and Patency Rates in Young and Elderly Patients Undergoing Extra–Intracranial Bypass Surgery - Croci, Davide M.; Farooq, Jeffrey; Monsour, Molly; Vakharia, Kunal; Lau, Tsz; Mhaskar, Rahul; Loveren, Harry van; Agazzi, Siviero (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
Extra–Intracranial (EC–IC) bypass surgery is an effective procedure to restore hemodynamic insufficiency and mitigating cerebral ischemia. With increasing life expectancy, the incidence of patients with hemodynamic insufficiency is expected to rise further. Here we aimed to analyze the complications and patency rate of patients ≥70 years that underwent EC–IC bypass and compare it with a younger cohort (<70 years).Patient charts were retrospectively reviewed for diagnosis, patient presentation, type of bypass, postoperative course, and follow-up. A total of 175 patients underwent arterial bypass during the study period. A total of 158 patients were <70 years old compared with 17 patients ≥70 years old.EC–IC bypass was performed with a scalp artery in 88.2% cases in the older group and 88.0% cases in the younger group. The younger group was more likely to undergo bilateral bypass (28.1%) than the older group (0%; p = 0.01). There were no significant differences in overall medical and surgical complication rates between older and younger patients undergoing arterial bypass (p = 0.61). Direct postoperative graft patency was similar between groups. Follow-up patency data were available in 97.7% of patients (average 18.0 ± 25.1 months). Graft patency rate at follow-up was 88.3%, with rates 88.2% in the older group and 88.3% in the younger group.Our data confirm previous data in the literature on the safety and efficacy of EC–IC Bypass in the elderly population. These results suggest that variables other than age may be more important in determining potential benefit from EC–IC bypass treatment.
Keywords: EC–IC bypass; stroke; elderly patients; ischemic stroke